Analysis of Factors Affecting Performance With Work Motivation As Intervening West Sumatra Shipping Polytechnic - Eliza, Yulina (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
This study aims to see the influence of 1) Leadership style on employee work motivation 2). Compensation for employee motivation 3). Work motivation on employee performance 4). Leadership style towards employee performance 5). Compensation for employee performance 6). Leadership style towards employee performance with work motivation as an intervening variable. 7). The effect of compensation on employee performance with work motivation as an intervening variable. The study's demographic and sample consisted of all 50 West Sumatra Shipping Polytechnic workers. the process of employing total sampling to calculate the number of samples. By meeting the conditions of the classical assumption test for normality, linearity, multicollinearity, and heteroscedasticity, the data analysis approach employs route analysis. The West Sumatra Shipping Polytechnic personnel' job motivation is significantly impacted by their leadership style and salary, according to the study's findings. In addition, salaries, job motivation, and leadership style all have a big impact on how well West Sumatra Shipping Polytechnic personnel perform. The study's recommendations include that West Sumatra Shipping Polytechnic pay attention to the leadership styles that emerge in workers at work, that the agency focus on raising compensation, and that increased work motivation be taken seriously since it will lead to an improvement in performance.